Designing human-machine interaction concepts for machine tool controls regarding ergonomic requirements. Issue 1 (July 2017) - Czerniak, Julia N.; Brandl, Christopher; Mertens, Alexander
Abstract: Controlling machine tools causes high mental strain levels for the operator due to tremendous machine functionality and process complexity. As a consequence, innovative human-machine interaction concepts are required. This paper discusses a morphological box as a method for selecting different technologies as a task suitable interaction concept for machine tool controls regarding ergonomic requirements, based on a comprehensive technology catalogue. As a result, we designed an interaction concept to optimize the operator's strain level, appropriate to the context of use of controlling and monitoring multiple machine tools.